EFFECT OF WATER STRESS ON OKRA YIELD AT VEGETATIVE STAGE - Farhan Ahmad Abdulrahman; Hawrez Ali Nadir (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2018)
This study was conducted in Technical College of Applied Sciences, Sulaimany Polytechnic University, during 2017. Different levels of irrigation were used to production of okra plant. Complete Randomize Design used to layout of the experiment, with three level of irrigation in four replications. Yield, fresh weight of plant, dry weight of plant, yield response factor and different levels of irrigation were observed. The highest yield was given from treatment T1 (3.17 t/ha.) and the lowest was given from T3 (2.988 t/ha.). Also, the maximum fresh weight and dry weight of plant were given from T1 (61.40, 11.218 t/ha.), and their minimum was given from treatment T3 (57.00, 8.783 t/ha.). The highest water use efficiency and harvest index were obtained from T3 (1.615 kg.m-3, 0.095), and the lowest was given from treatment T1 (1.055 kg.m-3, 0.094). The crop response factor and the results in this study showed that the okra plants have a good response of water stress. As a result, we can recommend cultivating the okra at that time without irrigation in that region.